THU0198 Baricitinib Effects on Lipid and NMR-Measured Lipoprotein Profiles in A Phase 3 Study in Patients with Rheumatoid Arthritis. (15th July 2016) - Taylor, P.; Keystone, E.; Tanaka, Y.; van der Heijde, D.; Zhong, J.; Thanabalasundrum, S.; Ruotolo, G.; Schlichting, D.; Rooney, T.P.; Macias, W.L.; Zuckerman, S.; de Bono, S.; et al.
Abstract : Background: Baricitinib (bari), a JAK1 and JAK2 inhibitor, was efficacious compared to placebo (PBO) and adalimumab (ADA) in a 52-week (Wk) Ph 3 study in patients (pts) with active rheumatoid arthritis (RA) and an inadequate response (IR) to methotrexate (MTX) 1 . Objectives: To evaluate changes in lipid and lipoprotein profile over 52 wks of treatment with bari or ADA compared with PBO in the aforesaid study. Methods: MTX-IR pts with active RA were randomized 3:3:2 to bari 4mg once daily (QD), PBO, or ADA 40mg biweekly. Lipid profile was evaluated at baseline and at Wks 12, 24, and 52 and nuclear magnetic resonance (NMR)-measured lipoprotein particle size and number at baseline and Wk 12. Results: Treatment with both bari and ADA resulted in significant mean increases from baseline to Wk 12 in total cholesterol (PBO -0.2%, bari 15%, ADA 7%), triglycerides (PBO 1%, bari 17%, ADA 12%), LDL-C (PBO -0.6%, bari 16%, ADA 9%), and HDL-C (PBO 0.8%, bari 17%, ADA 8%). These increases persisted through Wk 52. The NMR lipoprotein profile revealed similar changes for bari and ADA relative to PBO regarding an increase in large LDL, a decrease of all types of small LDL, and increases in IDL, VLDL and subfractions, and total HDL as well as large and small HDL particles (Table 1 ). Significant increases in total LDL particle numbers were not observed with either bari or ADA. Conclusions: The increase in LDL-C and HDL-C with both bari and ADA is accompanied by an increase in large LDL, total HDL particles and a decrease in small LDL. The nature of these changes may potentially indicate a more atheroprotective profile than that of the PBO group. References: Taylor et al. Arthritis Rheumatol 2015;67(suppl10). Abstract 2L. Disclosure of Interest: P. Taylor Grant/research support from: UCB, GlaxoSmithKline, Celgene, Consultant for: UCB, Eli Lilly & Company, Pfizer, Galapagos, Merck, GSK, AbbVie, Takeda, BMS, E. Keystone Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, F. Hoffman-La Roche Inc, Janssen, Eli Lilly & Company, Novartis, Pfizer, Sanofi-Aventis, Consultant for: Abbott, AstraZeneca, Biotest, BMS, F. Hoffmann-La Roche, Genentech, Janssen, Eli Lilly & Company, Merck, Pfizer, UCB, Speakers bureau: Abbott, Amgen, AstraZeneca, BMS Canada, F. Hoffmann-La Roche, Janssen, Pfizer, UCB, Y. Tanaka Grant/research support from: Mistubishi-Tanabe, Takeda, Chugai, Astellas, Eisai, Taisho-Toyama, Kyowa-Kirin, Abbvie, Bristol-Myers, Speakers bureau: Abbvie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, Eli Lilly, GlaxoSmithKline, UCB, Teijin, MSD, Santen, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Celgene, Daiichi, Eli Lilly & Company, Galapagos, Merck, Novartis, Pfizer, Roche, Sanofi-Aventis, UCB, Employee of: Director Imaging Rheumatology BV, J. Zhong Employee of: Quintiles Transnational, Inc, S. Thanabalasundrum Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, G. Ruotolo Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, D. Schlichting Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, T. Rooney Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, W. Macias Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. Zuckerman Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. de Bono Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, M. Weinblatt Grant/research support from: Crescendo Bioscience, Consultant for: Eli Lilly & Company, Crescendo Bioscience, Pfizer, AbbVie